Model Arsitektur Sistem Informasi Terintegrasi AI untuk Pemantauan dan Intervensi Anak dengan Autism Spectrum Disorder - Harkat Christian Zamasi; Arden Sagiterry Setiawan (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2026)
The increasing number of children with Autism Spectrum Disorder (ASD) in Indonesia shows a continuing upward trend; however, it is still confronted with various fundamental challenges, such as the low level of parental understanding regarding early detection, the limited availability of medical professionals and therapists, and the absence of an integrated information system and data center. These conditions result in diagnosis, therapy, and developmental data of children with ASD being scattered and not continuously documented. On the other hand, the advancement of information technology, particularly Artificial Intelligence (AI), offers significant potential in supporting early detection, behavioral analysis, and the provision of personalized and data-driven intervention recommendations. This study aims to design an abstract information system architecture model integrated with AI to support monitoring and intervention processes for children with ASD. The method used is the Design Science Research (DSR) approach, which includes stages of problem identification, model design, conceptual artifact development, and validation through use case scenarios. The study results in an integrated information system architecture model comprising user applications, a data integration layer, AI analytics modules, and a human-in-the-loop mechanism. The contribution of this study is an AI-based integrated conceptual information system framework designed to address the limitations of existing systems, which are generally fragmented and isolated and serves as a foundation for the development of ASD monitoring and intervention systems in Indonesia.